Soft Skills: A Practice or Process - G. Kiran Kumar Reddy, L. Zainab Themeen Khanam, S. Asma Banu (Mathematical Statistician and Engineering Applications, 2023)
This paper attempts to discuss soft skills. In recent generation, companies are frequently complaining at lapse of soft skills. Soft skills are in great demand. Games are helpful to enhance soft skills. Cooperation, coordination affects the work culture at the workplace. Due to lack of communication skills every organization suffers a lot in their professional lives. It explores team skills, ethics, time management skills , soft skills improvise vision, planning effective resume writing.